PRAKTIK PERLOMBAAN KICAU BURUNG DENGAN MERGER HADIAH DAN SINKRONISASI BIAYA TIKET PENDAFTARAN DALAM PERSPEKTIF HUKUM ISLAM: (Studi Kasus di Lapangan Alam Pesona Tebas Kuala) - Dian Fariani; Zarul Arifin; Asman Asman (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
This study aims to analyze how the practice of bird chirping competition with merger prizes and synchronization of registration ticket costs in the Alam Pesona Tebas Kuala field and how the bird chirping competition practice is based on Islamic law. This type of research is field research with descriptive qualitative research methods. The data collection techniques used are based on primary sources, namely interviews, observation and documentation in the field such as registration tickets, various kinds of prizes, chirping birds, informants, namely judges, participants, and the committee. And through secondary sources in the form of books related to this research. Based on the results of the research, it is concluded that the practice of the bird chirping competition with merger prizes and synchronization of registration ticket costs at the Alam Pesona Tebas Kuala field is a prize competition that prepares various kinds of prizes from several parties, namely from the sponsor, the committee in the form of a trophy and the participants in the form of cash collected from ticket purchases by participants. Based on Islamic law, the bird chirping competition is not in accordance with the principles of Islamic economics, which is to avoid maysir elements, because taking one of the competition prizes through the results of ticket purchases by participants is in the form of cash, so the law of cash prizes becomes haram. Because prize winners in the form of cash and trophies come from the committee, so the law to use the prizes is makruh